Key technologies and prototype validation research of integrated sensing and communications for low altitude UAV - ZHAO Chuanbin; ZHANG Tengyu; FENG Yuan; LUO Dongqi; GAO Feifei (物联网学报, 2025)
With the help of base station cellular networking, the integrated sensing and communications (ISAC) key technologies for 6G can communicate with low-altitude unmanned aerial vehicle (UAV) in a wide range of reliable low-time delay and large bandwidth, and detect, track and identify non-cooperative UAV. Firstly, the key technologies for single base station sensing UAV were analyzed. Then, based on the advantages of cellular base station networking, the key technologies of multi-mode accurate sensing UAV with multi-base station collaboration and vision fusion wireless were proposed. The beam optimization and resource management of multi-base station networking were studied. Finally, an ISAC hardware prototype platform was developed, which could perform UAV tracking and bird identification while maintaining communication services.